IMPLEMENTATION OF INTEGRATED REPORTING ON MARKET PERFORMANCE OF SOE COMPANIES IN INDONESIA - Khalida Utami; Widyawati; Ade Palupi; Muhammad Nurmisbah (FEB-UP Press, 2022)
This study aims to examine the implementation of IR elements which are still voluntary on market performance as measured using the Price earning ratio and stock prices. The sample used in this research is 20 state-owned companies which issue annual reports from 2018 to 2020. This study uses a multiple regression analysis tool by testing two research models, namely the first to test the implementation of IR on the price earning ratio, the second model to test the implementation IR on stock prices. The results in this study indicate that market performance as measured by stock prices is influenced by the disclosures of companies that implement IR. These results indicate that disclosure through IR causes investors to be better able to see and assess the company's prospects in the future so that the risks that must be borne by investors are reduced. Thus, a company's stock price can increase followed by an increase in information disclosure made by the company through the implementation of IR